2012
DOI: 10.1038/hr.2012.134
|View full text |Cite
|
Sign up to set email alerts
|

The effects of angiotensin receptor blockers vs. calcium channel blockers on the acute exercise-induced inflammatory and thrombotic response

Abstract: Arterial hypertension is an established risk factor for acute coronary syndromes, and physical exertion may trigger the onset of such an event. The mechanisms involved include the rupture of a small, inflamed, coronary plaque and the activation of thrombogenic factors. Blood pressure (BP)-lowering treatment has been associated with beneficial effects on subclinical inflammation and thrombosis at rest and during exercise. This prospective study sought to compare the effect of different antihypertensive drugs on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…The results of this study showed that the levels of plasma fibrinogen and serum IL-6 significantly increased after exercise in all groups, but there was no significant difference between the exercise environments (NN vs. HH). These results are consistent with previous studies [ 6 , 27 ] that demonstrated that acute exercise significantly increased the levels of fibrinogen and IL-6 in the blood by causing an inflammatory response, and suggest that exercising in an HH environment, which corresponds to conditions at an altitude of about 3000 m, did not lead to additional inflammatory responses compared to exercising in an NN environment. Liakos et al [ 6 ] reported that the levels of fibrinogen and IL-6 were significantly increased after maximal treadmill exercise testing using the Bruce protocol, and in Stelzer et al’s study [ 27 ], the levels of fibrinogen and IL-6 were analyzed to verify changes in the inflammatory response with ultra-endurance exercise.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of this study showed that the levels of plasma fibrinogen and serum IL-6 significantly increased after exercise in all groups, but there was no significant difference between the exercise environments (NN vs. HH). These results are consistent with previous studies [ 6 , 27 ] that demonstrated that acute exercise significantly increased the levels of fibrinogen and IL-6 in the blood by causing an inflammatory response, and suggest that exercising in an HH environment, which corresponds to conditions at an altitude of about 3000 m, did not lead to additional inflammatory responses compared to exercising in an NN environment. Liakos et al [ 6 ] reported that the levels of fibrinogen and IL-6 were significantly increased after maximal treadmill exercise testing using the Bruce protocol, and in Stelzer et al’s study [ 27 ], the levels of fibrinogen and IL-6 were analyzed to verify changes in the inflammatory response with ultra-endurance exercise.…”
Section: Discussionsupporting
confidence: 93%
“…Even though it is a necessary defensive reaction that helps damaged tissue to recover, it can also cause other diseases like cardiovascular disease [ 23 ] and is closely related to musculoskeletal damage and muscle fatigue [ 24 , 25 ]. In some previous studies [ 6 , 26 ], the levels of fibrinogen, IL-6, and TNF-α in the blood have been reported to be indices reflecting the inflammatory response induced by acute exercise. This study analyzed the levels of plasma fibrinogen, serum IL-6, and TNF-α to verify changes in the inflammatory response depending upon the exercise performed in NN and HH environments and investigated the effect of HBOT on recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, data regarding an interaction between ARBs and exercise in humans is sparse. One trial comparing ARBs to calcium channel blockers in hypertensive patients found ARBs to attenuate indicators of exerciseinduced inflammatory response and thrombogenic factor activation (Liakos et al 2012). However, similar interactions are not universal.…”
Section: Arb-exercise Interactionmentioning
confidence: 99%
“…Evidence from Caucasian populations show that inflammation associates with unhealthy lifestyle factors such as smoking [19,20], excessive alcohol consumption [16], physical inactivity [20,21], malnutrition [22] and psychological conditions [23].…”
Section: Introductionmentioning
confidence: 99%